A Decision Support Tool for Stakeholder Engagement in Sustainable Land Management using the WEFE Nexus: A simulation for the Aral Sea Basin stakeholders. BWM conference in Delft university - Verbist, Joren; Akramkhanov, Akmal (2024)
The present presentation describes about Decision Support Tool (DST) which was developed to consider the difficult and complex interplay of the Water-Energy-Food-Ecosystem (WEFE) Nexus in Aral Sea Basin region through Best Worst Method (BWM).